The Telematic solutions in plastic surgery during COVID-19 pandemic - De Santis, Giorgio; Palladino, Teresa; Leti Acciaro, Andrea; Starnoni, Marta (Acta Biomedica Atenei Parmensis, 2020)
During the COVID-19 pandemic, surgical elective procedures were stopped in our plastic surgery unit. Limitations for consultations and for follow-up of previous surgical procedures were imposed in order to minimize the risk of contagion in waiting rooms and outpatient clinics. We have identified telemedicine as an alternative way to follow patients during the lockdown. Nevertheless, we have experienced different difficulties. We have not had the possibility to use a secure teleconferencing software. In our unit we had not technological devices. Surgeons in our department were not able to use remote video technology for patient management. Guidelines for an appropriate selection of patients which could be served via telemedicine had to be created. Telemedicine must be regulated by healthcare organizations for legal, ethical, medico-legal and risk management aspects. Even if we have experienced an important need to use telematic solutions during the COVID-19 lockdown, liability and risk management issues has greatly limited this possibility in our unit. The need of telemedicine in the time of COVID-19 pandemic has encouraged us to implement future virtual encounters in order to reduce unnecessary in-person visits by taking into consideration all legal, ethical and medico-legal aspects.